Islamic religiosity and its impact on Muslim men's share of housework and childcare time in Malaysia: A proxy investigation - Harn Shian Boo (Social Sciences and Humanities Open)
Malaysia is well-known as an Islamic country, with about two-thirds of the people believing in the Islamic religion and identifying themselves as Muslims. The Islamic religion significantly shapes the gendered expectations for Muslim men and women in the household, but it's unclear how religiosity influences Muslim men's share of housework and childcare time in Malaysia. The research objectives of this study are to examine the relationship between Islamic religiosity and Muslim men's share of housework and childcare time in Malaysia. By using quantitative research methods, five hundred seventy-six participants (female participants) took part in the online survey. An ordinary least squares (OLS) regression analysis shows that the Islamic religiosity of both women and men is associated with Muslim men's share of housework and childcare time in Malaysia. The findings suggest a positive relationship between men's religiosity and their share in housework and childcare time. That is, when Muslim men are more religious, they tend to contribute a greater amount of housework and childcare time compared to less religious Muslim men. In addition, the findings suggest a negative relationship between women's religiosity and men's share in housework and childcare time. Muslim men tend to contribute more time to housework and childcare when their wives have lower levels of Islamic devotion. This study focusing on Islam, argues the positive association between Muslim men's religiosity and their share of housework and childcare time in Malaysia. This study suggests that the higher level of Islamic religiosity encourages Muslim men to participate more in housework and childcare, perhaps it can lead to a more equal distribution of responsibilities within the household, irrespective of traditional gender roles. In sum, this quantitative study contributes to the existing knowledge by emphasising the significance of Islamic religiosity and housework and childcare sharing among Muslim couples in Malaysia.